Effect of Deferred Tax Expense and Discretionary Accrual on Earnings Management - Darwis Lannai (Manunggal Halim Jaya, 2022)
This study aims to examine and analyze the effect of Deferred Tax Expense and Discretionary Accrual on Earnings Management in Food and Beverage Sub-Sector Companies listed on the Indonesia Stock Exchange (IDX). The data in this study were obtained from the website.idx.id and the Capital Market Information Corner of the Indonesian Muslim University as many as 26 companies. The sample was selected using the purposive sampling method with the criteria. Namely, companies listed on the Indonesia Stock Exchange, publishing financial statements for the year ended December 31 during 2013-2017, not experiencing suspension during the observation period, reporting financial statements in Rupiah (IDR) ), and suffered no losses the study period. Furthermore, the data were analyzed using descriptive statistics, and the hypothesis was tested multivariate using logistic regression. The results showed that deferred tax expense had no significant effect on earnings management and discretionary accruals had no significant effect on earnings management.